Effects of a Multicomponent Life-Style Intervention on Weight, Glycemic Control, Depressive Symptoms, and Renal Function in Low-Income, Minority Patients With Type 2 Diabetes: Results of the Community Approach to Lifestyle Modification for Diabetes Randomized Controlled Trial. Issue 7 (September 2016) - Moncrieft, Ashley E.; Llabre, Maria M.; McCalla, Judith Rey; Gutt, Miriam; Mendez, Armando J.; Gellman, Marc D.; Goldberg, Ronald B.; Schneiderman, Neil
ABSTRACT: Objective: Few interventions have combined life-style and psychosocial approaches in the context of Type 2 diabetes management. The purpose of this study was to determine the effect of a multicomponent behavioral intervention on weight, glycemic control, renal function, and depressive symptoms in a sample of overweight/obese adults with Type 2 diabetes and marked depressive symptoms. Methods: A sample of 111 adults with Type 2 diabetes were randomly assigned to a 1-year intervention ( n = 57) or usual care ( n = 54) in a parallel groups design. Primary outcomes included weight, glycosylated hemoglobin, and Beck Depression Inventory II score. Estimated glomerular filtration rate served as a secondary outcome. All measures were assessed at baseline and 6 and 12 months after randomization by assessors blind to randomization. Latent growth modeling was used to examine intervention effects on each outcome. Results: The intervention resulted in decreased weight (mean [M] = 0.322 kg, standard error [SE] = 0.124 kg, p = .010) and glycosylated hemoglobin (M = 0.066%, SE = 0.028%, p = .017), and Beck Depression Inventory II scores (M = 1.009, SE = 0.226, p < .001), and improved estimated glomerular filtration rate (M = 0.742 ml·min −1 ·1.73 m −2, SE = 0.318 ml·min −1 ·1.73 m −2, p = .020) each month during the first 6 months relative to usual care. Conclusions: Multicomponent behavioral interventions targeting weight loss and depressive symptoms as well as diet and physical activity are efficacious in the management of Type 2 diabetes. Trial Registration: This study is registered at Clinicaltrials.gov ID: NCT01739205. Abstract : Supplemental digital content is available in the text.